The Retroactive Principle in Law No. 26 of 2000 concerning the court of human rights - Ricky Tongam Marpahala Siahaan; Candra Perbawati; Ahmad Saleh (Constitutionale, 2020)
Protection of human rights is a responsibility that must be carried out by the state, in this case the state must also resolve cases of human rights violations that have occurred. There are many cases of human rights violations that occurred in the past but cannot be resolved because there are no legal rules that govern at that time. The presence of Law Number 26 of 2000 concerning the court of human rightss is certainly a way for the government to resolve the problem of gross human rights violations in the past. The principle of retroactivity was included in Law Number 26 of 2000 concerning the court of human rightss so that gross violations of human rights that occurred in the past could be resolved. The retroactive principle in Law Number 26 of 2000 concerning the court of human rightss is considered to violate existing regulations in Indonesia, especially it is considered contrary to the 1945 Constitution. -Law Number 26 of 2000 concerning the court of human rightss. This research uses normative research methods. The data used are secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study indicate that the application of the retroactive principle in Law Number 26 of 2000 concerning the court of human rightss does not contain elements that are absolutely contradictory to the Law. 1945 foundation.